1982
DOI: 10.1007/bf01657673
|View full text |Cite
|
Sign up to set email alerts
|

Basal and dose‐response studies of gastric mucosal blood flow: Comparison of duodenal ulcer patients before and after highly selective vagotomy with normal volunteers

Abstract: Gastric mucosal blood flow (neutral red clearance, NRC) and acid secretion were measured before and after highly selective vagotomy (HSV). Eleven patients with duodenal ulcer were studied before and 12–21 days after HSV. Eight volunteers were also studied using the histamine‐H2‐receptor antagonists cimetidine and ranitidine. Basal secretion was collected for 40–50 minutes and pentagastrin was given in increasing doses each for 40 minutes. Data were analyzed using Wilcoxon's signed‐ranks test for paired samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1986
1986
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Intraoperative measurements with LDF before and after PGV have shown similar results along the devascularized part of the lesser curvature [17]. Using neutral red, McIsaac et al [18] found unchanged blood flow in patients 2-3 weeks after PGV, and measurements with LDF have shown similar results [17]. These findings and the results of the present study show that a normalization of the blood flow to preoperative values takes place during the weeks after the operation.…”
Section: Discussionsupporting
confidence: 85%
“…Intraoperative measurements with LDF before and after PGV have shown similar results along the devascularized part of the lesser curvature [17]. Using neutral red, McIsaac et al [18] found unchanged blood flow in patients 2-3 weeks after PGV, and measurements with LDF have shown similar results [17]. These findings and the results of the present study show that a normalization of the blood flow to preoperative values takes place during the weeks after the operation.…”
Section: Discussionsupporting
confidence: 85%
“…Knight et al [f9] concluded that the concentration of hydrogen ions secreted is proportional to blood flow, whereas, on the other hand. Me Isaac et al [21] did not find any correla tion. The argument is not convincing with regard to the relationship between GMBF and cimetidine [20], vagotomy [14] or splanchnic sympathectomy [12], The investi gations should be continued with more fre quent use of the laser Doppler interface for continuous experimental measurement of GMBF.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the beneficial effects obtained with NaHCO, confirm the significance of mucosal cytoprotcction against the increased secretion of hy drogen ions. Like Ritchie, we have concluded that the H2 antagonist is ineffective [4], Unanimity has not yet been achieved with regard to the relationship established be tween GMBF, acid secretion and mucosal protection [5,12,21]. Varhaug [36] found a correlation between the reduction in the acid secretion and the diminution of GMBF after devascularization [36], whereas Cheung and Lowry [5] observed a diminution of the mu cosal acid secretion despite an increase of GMBF when they administered a continuous infusion of prostaglandin E|.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with 14C aminopyrine clearance, neutral red clearance, and 9 9 m T~ clearance have shown increased blood flow after stimulation of acid secretion (6,9,10). However, questions have been raised concerning the reliability of the aminopyrine clearance technique and the use of neutral red clearance in man (22,23).…”
Section: After Pentagastrinmentioning
confidence: 98%